DISIPLIN BELAJAR WARGA BELAJAR DALAM MENGIKUTI PROSES BELAJAR MENGAJAR DI PANTI SOSIAL BINA REMAJA RUMBAI PEKANBARU - Murti Ayu Natalia Nadeak Ayu Natalia Nadeak; Daeng Ayub Natuna Ayub Natuna; Jasfar Jas Jasfar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems of this study is the high level of discipline of learning How residents learned in following the teaching and learning process in the Young Children's Social Development Rumbai Pekanbaru? The benefits of research to increase knowledge on matters relating to Citizens Learning Learning Discipline, especially for researchers. This study will be useful for all coaches who provide guidance to citizens of learning. This is a descriptive study with a quantitative approach which aims to describe the results of research by the numbers. The sampling technique using simple random sampling (random sampling). Data collection techniques in this research is to use the questionnaire as a method of data collection, which totaled 54 item statement. After the questionnaire in the trial, there are four items that are not valid. Data obtained from respondents who totaled 25 people to sample the test and 43 people with Alpha Cronbach = 0.565 Based on the research findings obtained discipline of learning people learn to follow PBM in the Young Children's Social Development Rumbai Pekanbaru based indicator Complying with the rules of the respondents were high levels of discipline that is 93.02%. Indicators not like to lie a high level of discipline that is 88.36%, the indicators diligent in learning the high level of discipline that is 90.23%, an indicator not rely on other people a high degree of discipline that is 86.83%, Indicators Timely high level of discipline ie 80.69%, Indicator Obey the rules of the high level of discipline that is 90.40%, The average score of the mean of each indicator is very high this can be seen from indicator Complying with the rules with a mean of 4.42 and 0.65 SD. indicators not like lying obtained a mean value of 4.32 and 0.80 SD. Indicator diligent in learning the obtained mean values of 4.39 and 0.77 SD. Indicators not rely on other people obtained a mean value of 4.34 and 0.72 SD. Timely indicators mean values obtained 4.29 and 0.77 SD. Obey the rules of the indicators obtained a mean value of 4.35 and 0.72 SD all indicators are at very high interpretation. Having done the research and data processing can be concluded that the learners have a very high level of discipline. Therefore for the coach and the leadership of the Young Children's Social Development Rumbai expected to further increase the level of discipline to the learners.Keywords: Discipline, discipline of learning, learners, PSBR2DISIPLIN BELAJAR WARGA BELAJAR DALAM MENGIKUTI